Structural behaviour of tubular joints under elevated temperature - Teo, Raymond Zhia Wee. (2009)
Judging from widespread use of steel tubular joints and its increasing importance in both construction and offshore industry, an investigation on the behavior of such joints under transient elevated temperature was conducted. The main focus for this FYP will be to observe the behavior of one of such joints, the T-joint, under transient temperature. Transient temperature analysis is considered as a more practical approach due to its close resemblance to a fire breakout. In this analysis, the stress history of each level of temperature will be captured and portrayed clearly in the subsequent steps. A numerical model of a tubular T-joint was constructed and subjected to axial and bending loads under transient elevated temperature. The FE modeling was done using the ABAQUS/Standard v6.7-1 commercial package. Input parameters for the model were sourced from Eurocode 3 Part 1-2 (2005) for the properties for material models for different temperatures. The model was verified with a similar model for isothermal temperature subjected to the same levels of temperature increase. Total stress levels for the joint under different temperatures under the same time period were plotted. It was noted that the trends of the graphs can be explained by existing stress and temperature relationships. Some irregularities were found in the graph plots for elements along the chord, and a possible explanation was formulated to justify the findings. It was also found that the final total stress levels after cooling down to ambient temperature were significantly higher than the initial stress levels at ambient temperature. A probable explanation for this was attributed to formation of plastic hinges during elevated temperatures. In addition, the stress contours at various stages of the analysis was also plotted. The objective of this is to capture the possible mode of failures during different stages. The two main mode of failures observed were the local chord plastification failure and the in-plane chord bending failure. The reduction of yield strength and stiffness of the material was employed to explain the changes in the stress contours and the different modes of failure. It was also noticed that the changes of the stress contours after cooling down to ambient temperature is not as predicted. The reasons were further elaborated. From this FYP, it can be concluded that different temperatures can influence the stress levels and mode of failures in steel tubular joints, due to changes in stress concentrations. Given the fact that this FYP is preliminary investigation through FE modeling and analysis, future experimental work can be conducted to validate the results generated by the FE model.